Hydrothermal Synthesis and Structure of a 3D-Supramolecular Complex: phen-Cu-C2O4 - Bi, Jian-Hong (Asian Journal of Chemistry, 2010)
The complex Cu[(phen)(C2O4)(H2O)]·H2O, where phen = 1,10-phenanthroline, has been synthesized and its crystal structure were determined by X-ray diffraction. Crystal data: monoclinic, space group P2(1)/n, a = 8.457 Å, b = 9.70580(10) Å, c = 17.45100(10) Å, α = 90º, β = 103.8190(10)º, γ = 90º, V = 1391.016(16)Å3, Z = 4, Mr = 367.80, Dc = 1.756 Mg/cm3, μ = 1.605 mm-1, F(000) = 748, T = 273(2) K, R = 0.0292, wR = 0.0735 for 2460 observed reflections (I > 2σ(I)). The center Cu(II) ion is coordinated by five atoms in a slightly distorted square pyramidal geometry. The compound is in 3D supramolecular state.